D2.3 An ex-vivo model for the incorporation of immunoadsorption into the extracorporeal circuit: a novel method for abo incompatible heart transplantation. (4th October 2017) - Robertson, A; Issitt, R; Crook, R; Gustafsson, K; Eddaoudi, A; Tsang, V; Burch, M
Abstract : Background: Since 1996, ABO- incompatible heart transplants have been undertaken by carrying out a whole body plasma exchange to remove isohaemagglutinins using the cardiopulmonary bypass circuit at the time of transplantation. However, this requires large volumes of donated blood and blood products, causes haemodynamic instability during the exchange transfusion and limits the practical usage to small children. We sought to determine the efficacy of anti-A/B immunoadsorption within the cardiopulmonary bypass circuit on removal of isohaemagglutinins in an ex vivo setting. Methods: An anti-A/B immunoadsorption column was placed into a CPB circuit mimicking a typical ABO-incompatible transplant patient, which had been primed with group O whole human blood. Samples were taken for determination of isohaemagglutinin titres following each plasma volume pass through the anti-A/B immunoadsorption column. Results: There was a linear decrease of at least one dilution seen in both anti-A and -B IgG and IgM antibodies with each plasma volume pass through the column. This predictable removal allowed the formulation of selection criteria for ABO-incompatible heart transplantation given the reciprocal of titre and patient weight. Conclusions: The incorporation of an anti-A/B immunoadsorption column into the extracorporeal circuit reduces the allogeneic blood product requirement for ABO-incompatible heart transplantation whilst providing efficacious removal of anti-A and anti-B isohaemagglutinins. Furthermore, this can be undertaken within the time period of cardiopulmonary bypass before graft reperfusion and expands the potential recipient pool to larger patients with higher isohaemagglutinin titres. Further work is now planned to examine the possibility of utilising similar technology for HLA-incompatible heart transplants, and to create a 3rd generation cloud–based transplant registry that will link outcomes, genetics and antibody profiles from centres Worldwide.